Development of a pressure-induced triploidy protocol and its effects on growth performance and fertility in tambaqui Colossoma macropomum (Cuvier, 1816) - Aldessandro da C. Amaral; Lucas S. Torati; Luciana N. Ganeco-Kirschnik; Luciana C.V. Villela; André Silverio Pereira; Julia T. Lopes; Yury O. Chaves; Diogo T. Hashimoto; Velmurugu Puvanendran; Fernanda L. Almeida O'Sullivan (Aquaculture, 2026)

Deep learning approach for genetic selection of stress response in the Amazon fish Colossoma macropomum - Celma G. Lemos; Baltasar F. Garcia; Marcelo S.S. Filho; Jairo R. Arango; Arno J. Butzge; Luciana Shiotsuki; Luiz Eduardo L. Freitas; Fabrício P. Rezende; Elisabeth C. Urbinati; Guilherme J.M. Rosa; Diogo T. Hashimoto (Aquaculture, 2025)

Speciation of cesium in a radiocesium-bearing microparticle emitted from Unit 1 during the Fukushima nuclear accident by XANES spectroscopy using transition edge sensor - Yoshio Takahashi; Hikaru Miura; Shinya Yamada; Oki Sekizawa; Kiyofumi Nitta; Tadashi Hashimoto; Takumi Yomogida; Akiko Yamaguchi; Shinji Okada; Takaaki Itai; Hiroki Suga; Teruhiko Kashiwabara; et al. (Journal of Hazardous Materials, 2025)

Genetic selection for resistance to Francisella orientalis shows significant selection response in Nile tilapia - Baltasar F. Garcia; Jairo A. Restrepo-Arango; Marcelo S. Silva Filho; Elielma L. Sousa; John F.G. Agudelo; Vito A. Mastrochirico-Filho; Shisley C.S. Manso; Carolina S. Pereira; Danielle C. Dias; Antonio F.G. Leonardo; Fernando S. Fonseca; Leonardo Tachibana; et al. (Aquaculture, 2025)

Therapeutic effects of anti-amyloid β antibody after intravenous injection and efficient nose-to-brain delivery in Alzheimer’s disease mouse model - Noriyasu Kamei; Ayaka Hashimoto; Erina Tanaka; Kaho Murata; Maika Yamaguchi; Natsuki Yokoyama; Masahiro Kato; Keisuke Oki; Takashi Saito; Takaomi C. Saido; Mariko Takeda-Morishita (Drug Delivery and Translational Research, 2022)

Strategic roadmap to assess forest vulnerability under air pollution and climate change - Alessandra De Marco; Pierre Sicard; Zhaozhong Feng; Evgenios Agathokleous; Rocio Alonso; Valda Araminiene; Algirdas Augustatis; Ovidiu Badea; James C. Beasley; Cristina Branquinho; Viktor J. Bruckman; Alessio Collalti; et al. (Global Change Biology, 2022)
Although it is an integral part of global change, most of the research addressing the effects of climate change on forests have overlooked the role of environmental pollution. Similarly, most studies investigating the effects of air pollutants on forests have generally neglected the impacts of climate change. We review the current knowledge on combined air pollution and climate change effects on global forest ecosystems and identify several key research priorities as a roadmap for the future. Specifically, we recommend (1) the establishment of much denser array of monitoring sites, particularly in the South Hemisphere; (2) further integration of ground and satellite monitoring; (3) generation of flux‐based standards and critical levels taking into account the sensitivity of dominant forest tree species; (4) long‐term monitoring of N, S, P cycles and base cations deposition together at global scale; (5) intensification of experimental studies, addressing the combined effects of different abiotic factors on forests by assuring a better representation of taxonomic and functional diversity across the ~73,000 tree species on Earth; (6) more experimental focus on phenomics and genomics; (7) improved knowledge on key processes regulating the dynamics of radionuclides in forest systems; and (8) development of models integrating air pollution and climate change data from long‐term monitoring programs.

The role of dispersed ash in orbital-scale time-series studies of explosive arc volcanism: insights from IODP Hole U1437B, Northwest Pacific Ocean - Kate Corry-Saavedra; Julie C. Schindlbeck; Susanne M. Straub; Masafumi Murayama; Louise L. Bolge; Arturo Gómez-Tuena; Yoshitaka Hashimoto; Jon D. Woodhead (International Geology Review, 2019)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Impact of natural and calcined starfish (Asterina pectinifera) on the stabilization of Pb, Zn and As in contaminated agricultural soil - Jung Eun Lim; Jwa Kyung Sung; Binoy Sarkar; Hailong Wang; Yohey Hashimoto; Daniel C. W. Tsang; Yong Sik Ok (Environmental Geochemistry and Health, 2017)

Effects of the potential lithium-mimetic, ebselen, on brain neurochemistry: a magnetic resonance spectroscopy study at 7 tesla - Charles Masaki; Ann L. Sharpley; Beata R. Godlewska; Adam Berrington; Tasuku Hashimoto; Nisha Singh; Sridhar R. Vasudevan; Uzay E. Emir; Grant C. Churchill; Philip J. Cowen (Psychopharmacology, 2016)

A new species of Trichodina Ehrenberg, 1830 (Ciliophora: Trichodinidae) from Rhamdia quelen (Siluriformes: Heptapteridae) and Gymnotus sp. (Teleostei: Gymnotidae) in Brazil - Gabriela S.O. Hashimoto; Natalia C. Marchiori; Santiago B. Pádua; Márcia M. Ishikawa; Juan R.E. Garcia; Maurício L. Martins (Acta Parasitologica, 2016)
The present study describes a new species of

Reductions in synaptic proteins and selective alteration of prepulse inhibition in male C57BL/6 mice after postnatal administration of a VIP receptor (VIPR2) agonist - Yukio Ago; Michael C. Condro; Yossan-Var Tan; Cristina A. Ghiani; Christopher S. Colwell; Jesse D. Cushman; Michael S. Fanselow; Hitoshi Hashimoto; James A. Waschek (Psychopharmacology, 2015)

Development and characterization of microsatellite loci in Phractocephalus hemioliopterus (Siluriformes: Pimelodidae) and their cross-species amplification in six related species - C. A. Souza; D. T. Hashimoto; L. H. G. Pereira; C. Oliveira; F. Foresti; F. Porto-Foresti (Conservation Genetics Resources, 2012)

Identification and characterization of polymorphic microsatellite loci in the blue shark Prionace glauca , and cross‐amplification in other shark species - F. F. Mendonça; L. H. F. Ussami; D. T. Hashimoto; L. H. G. Pereira; F. Porto‐Foresti; C. Oliveira; O. B. F. Gadig; F. Foresti (Journal of Fish Biology, 2012)
Two to 14 alleles were found to be segregating per locus (mean 5·2), with observed and expected heterozygosities ranging from 0·08 to 0·78 and 0·08 to 0·94, respectively. Cross‐amplification of six of these microsatellite loci indicated that they are also polymorphic in three species of Carcharhiniformes and two species of Lamniformes. The newly developed primers reported here constitute a useful tool for genetic population analyses on Prionace glauca and, potentially, other related species.

Genetic identification of lamniform and carcharhiniform sharks using multiplex-PCR - F. F. Mendonça; D. T. Hashimoto; B. De-Franco; F. Porto-Foresti; O. B. F. Gadig; C. Oliveira; F. Foresti (Conservation Genetics Resources, 2010)

Evolution of host breadth in broad interactions: mycorrhizal specificity in East Asian and North American rattlesnake plantains (Goodyera spp.) and their fungal hosts - RICHARD P. SHEFFERSON; CHARLES C. COWDEN; MELISSA K. MCCORMICK; TOMOHISA YUKAWA; YUKI OGURA-TSUJITA; TOSHIMASA HASHIMOTO (Molecular Ecology, 2010)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Hypoxia-induced hyaluronan synthesis by articular chondrocytes: the role of nitric oxide - K. Hashimoto; K. Fukuda; K. Yamazaki; N. Yamamoto; T. Matsushita; S. Hayakawa; H. Munakata; C. Hamanishi (Inflammation Research, 2006)

Genetic diversity and phylogeny of Japanese sake-brewing rice as revealed by AFLP and nuclear and chloroplast SSR markers - Z. Hashimoto; N. Mori; M. Kawamura; T. Ishii; S. Yoshida; M. Ikegami; S. Takumi; C. Nakamura (Theoretical and Applied Genetics, 2004)

Involvement of proteases in glycosyltransferase secretion: Alzheimer's β-secretase-dependent cleavage and a following processing by an aminopeptidase - Shinobu Kitazume; Minoru Suzuki; Takaomi C. Saido; Yasuhiro Hashimoto (Glycoconjugate Journal, 2004)

Alzheimer's β-secretase cleaves a glycosyltransferase as a physiological substrate - Shinobu Kitazume; Takaomi C. Saido; Yasuhiro Hashimoto (Glycoconjugate Journal, 2003)

Peripheral nerve regeneration through alginate gel: analysis of early outgrowth and late increase in diameter of regenerating axons - T. Hashimoto; Y. Suzuki; M. Kitada; K. Kataoka; S. Wu; K. Suzuki; K. Endo; Y. Nishimura; C. Ide (Experimental Brain Research, 2002)

Simulation of the Transition of Earthquake Rupture from Quasi-static Growth to Dynamic Propagation - E. Fukuyama; C. Hashimoto; M. Matsu'ura (Pure and Applied Geophysics, 2002)

3-D Simulation of Earthquake Generation Cycles and Evolution of Fault Constitutitve Properties - C. Hashimoto; M. Matsu'ura (Pure and Applied Geophysics, 2002)

Construction of a high-resolution linkage map of a rice brown planthopper (Nilaparvata lugens Stål) resistance gene bph2 - H. Murai; Z. Hashimoto; P. N. Sharma; T. Shimizu; K. Murata; S. Takumi; N. Mori; S. Kawasaki; C. Nakamura (Theoretical and Applied Genetics, 2001)

In vitro characterization of J-113397, a non-peptide nociceptin/orphanin FQ receptor antagonist - R. Bigoni; G. Calo'; A. Rizzi; R. Guerrini; C. De Risi; Y. Hashimoto; E. Hashiba; D.G. Lambert; D. Regoli (Naunyn-Schmiedeberg's Archives of Pharmacology, 2000)

Retrolyc1-1, a member of the Tntl retrotransposon super-family in the Lycopersicon peruvianum genome - Ana Paula P. Costa; Katia C. Scortecci; Regina Y. Hashimoto; Paula G. Araujo; Marie-Angele Grandbastien; Marie-Anne Van Sluys (Genetica, 1999)

Dynamic changes in corticospinal excitability during motor imagery - Ritsuo Hashimoto; J. C. Rothwell (Experimental Brain Research, 1999)

Mixture in the distribution of haloperidol-induced oral dyskinesias in the rat supports an animal model of tardive dyskinesia - Takeshi Hashimoto; David E. Ross; Xue-Min Gao; Deborah R. Medoff; C. A. Tamminga (Psychopharmacology, 1998)

Molecular systematics of vestimentiferan tubeworms from hydrothermal vents and cold-water seeps - M. B. Black; K. M. Halanych; P. A. Y. Maas; W. R. Hoeh; J. Hashimoto; D. Desbruyères; R. A. Lutz; R. C. Vrijenhoek (Marine Biology, 1997)

Molecular cloning and sequence determination of the peplomer protein gene of feline infectious peritonitis virus type I - K. Motokawa; T. Hohdatsu; C. Aizawa; H. Koyama; H. Hashimoto (Archives of Virology, 1995)

Preparation of Japanese encephalitis virus nonstructural protein NS1 obtained from culture fluid of JEV-infected Vero cells - T. Lee; K. Watanabe; C. Aizawa; A. Nomoto; H. Hashimoto (Archives of Virology, 1991)

Effect of visible light on carotenogenesis in arthroconidiating Trichophyton mentagrophytes - Ruth C. Mock; Tadayo Hashimoto (Archives of Microbiology, 1984)